Tatak Pilipino [episode no. 50] [videorecording]. ([Quezon City ABS-CBN], 1991)
A unique display of Pilipino ways and style.
One year anniversary of Tatak Pilipino (5 min.) -- Pistang Pinoy with birthday celebration of Gel Santos Relos (15 min.) -- Fireworks and firecrackers (5 min.) -- Ramadan (5 min.) -- Balagtasan of Gel's life story (15 min.).
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Relos, Josefina Santos; Tatak Pilipino; Festivals -- Philippines; Firecrackers -- Philippines; Fireworks -- Philippines; Ramadan -- Philippines